A Multibiomarker Approach to Assess the Health State of Coastal Ecosystem Receiving Desalination Plants in Agadir Bay, Morocco - Ahmed Elazzaoui; Abdellatif Moukrim; Latifa Lefrere (The Scientific World Journal)
The present study aims to evaluate the initial health status of two stations receiving seawater desalination plants in Agadir Bay (Tifnit-Douira and Cap Ghir) and to assess their potential environmental impact on the marine ecosystem health. Six pairs of mussels (Mytilus galloprovincialis) were collected at six sampling sites on a monthly basis over two years. Each pair was homogenized to obtain the postmitochondrial fractions (S9). Toxicological effects were measured using a multibiomarker approach based on either acetylcholinesterase (AChE), glutathione S-transferase (GST), catalase (CAT), and malondialdehyde (MDA) rate. The results show a seasonal variation of the biomarkers: their activities increase in summer and decrease in spring and winter. High activities were recorded during summer in Cap Ghir (17.94 ± 0.88; 5.91 ± 052 nmol/min/mg of protein) for CAT and MDA, respectively. In Tifnit-Douira, low activities were recorded during winter for GST (3.74 ± 0.52 nmol/min/mg of protein) and during spring for the CAT (3.52 ± 0.45 nmol/min/mg of protein). The fluctuations in the activities of measured biomarkers could be attributed to different factors including the changes in environmental parameters, the influence of seasonal variation, and the contamination of the aquatic ecosystem. The data obtained in this study should be taken into account in the monitoring and management of the health of the ecosystems when the desalination plants are established.